Ambidextrous AI Governance Design Based on COBIT 2019 Traditional and DevOps for TelCo’s Digital Transformation - Putri, Nasywah Nabilah; Mulyana, Rahmat; Adi, Taufik Nur (TIERS Information Technology Journal, 2025)
Artificial intelligence (AI) is a key enabler of digital transformation in telecommunications, improving operational efficiency and customer experience. However, telecom companies face governance challenges such as regulatory compliance risks, security vulnerabilities, and limited risk management capabilities, hindering effective AI adoption. This case study aims to address AI adoption challenges by developing an ambidextrous AI governance framework based on COBIT 2019 and DevOps. Using design science research methodology, the framework was designed and evaluated through semi-structured interviews with key TelCo stakeholders and validated with internal documents until data saturation was reached. The analysis applied the ambidextrous COBIT 2019 framework across seven governance components. Governance and Management Objectives (GMOs) were prioritized based on design factors, devops,  national regulations (SOE Minister No.PER-2/MBU/03/2023 and ICT Minister No.5/2021), and literature. As a result, APO12 (Managed Risk) was selected as the key objective. Recommendations include formalizing AI governance roles, enhancing AI-related risk training, and implementing advanced GRC and automation tools. This improvement will increase the APO12 maturity level from 3.83 to 4.66. This improvement will enhance TelCo’s capabilities in risk management, compliance, and innovation, offering practical insights for practitioners and contributing to the academic discourse on ambidextrous AI governance for sustainable digital transformation.